User Experience Evaluation of e-Puskesmas in Payakumbuh City using the User Experience Questionnaire Method - Furqan Anwari; Eki Saputra; Arif Marsal; Mona Fronita; Muhammad Jazman; Syafril Siregar (INOVTEK Polbeng - Seri Informatika, 2025)
Puskesmas in Indonesia are responsible for providing primary health services to the local community. The Community Health Centers (Puskesmas) in Indonesia utilise e-Puskesmas, a web-based system that enables electronic data management and patient services. The newest version, e-Puskesmas Next Generation (NG), was made to allow online interactions, but it has had some technical problems, including duplicate medical data and wrong medication dosages because it doesn't have an allergy detection feature. The UEQ method will be used to rate the user experience of e-Puskesmas. The UEQ measures six factors: attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. Twenty-one people participated in the evaluation, and the results show that all variables were close to neutral. This means that using the system doesn't make people very happy or sad, but instead stays at an average level. This study confirms that, although e-Puskesmas has the potential to be an effective tool, there is still significant room for improvement, especially in terms of feature customisation and user interface. The "poor" score in the benchmark evaluation indicates that significant improvements in the system's design and functionality are necessary to enhance user satisfaction and healthcare service efficiency. It is hoped that these findings can encourage further development that addresses the existing shortcomings and effectively improves the management of health services at the community health centre